The Enduring Importance of Parenting: Caregiving Quality and Fear-Potentiated Startle in Emerging Adults With a Child Maltreatment History. (February 2023) - Sullivan, Alexandra D. W.; Brier, Zoe M. F.; Legrand, Alison C.; van Stolk-Cooke, Katherine; Jovanovic, Tanja; Norrholm, Seth D.; Garavan, Hugh; Forehand, Rex; Price, Matthew
Background: The transition to adulthood is a period of increased risk for emergent psychopathology; emerging adults with a childhood maltreatment history are at risk for poor outcomes.Method: Using a multi-measure, transdisciplinary, cross-sectional design, this study tested whether participant-reported positive parenting, a potential resilience-promoting factor, moderated the association between clinician-rated PTSD symptom severity and a transdiagnostic maladjustment biomarker, fear-potentiated startle (FPS), in a sample of 66 emerging adults ( M years = 18.83, SD = 0.89) with a maltreatment history. We hypothesized that characteristics of effective parenting would moderate the relation between PTSD symptoms and FPS.Results: Results indicated that elevated PTSD, as measured by the CAPS, was associated with a more severe startle reaction. The magnitude of the increase in startle reactivity was moderated by parenting such that those with more positive parenting (Accepting [relative to rejecting]: b = −0.42, p < .001; Psychologically-controlling [relative to autonomy-promoting]: b = 2.96, p = .004) had significantly less reactivity across the task at higher levels of PTSD symptoms.Conclusions: Emerging adults with childhood maltreatment histories, high levels of PTSD symptoms, and who perceive present-day high-quality caregiver support may cope better with novel stressors relative to youth lacking that support, potentially translating to better psychological outcomes.